Pengaruh Punishment Dan Reward Terhadap Disiplin Kerja Pada PT. Tri Mandiri Selaras Di Tenggarong - Syanti Wahyuni; Sabran Sabran; Muhammad Hermanto (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2022)
Abstract :           PT Tri Mandiri Selaras is a showroom company of Daihatsu cars equipped with authorized workshops for routine checks and maintenance as well as vehicle engine repair customers who are located on Aji Lake RT.05 Malay Village Kutai Kartanegara Regency. The number of employees working on PT Tri Mandiri Selaras are 26 people divided into 7 people mechanics, 6 administrators, 4 sales people, 2 office boys, 2 cashiers, 1 person, 1 head marketing and 3 human resouch developmen. The study was conducted in April 2018, the population data available in April 2018 was 25 people and the number of samples used in this study were 25 people. The analysis tools used are multiple regression analysis and hypothesis testing using F test and t test with the help of SPSS For Window 20.0. The results of F test calculations (simultaneous correlation / joint), variable punisment (X1) and reward (X2) simultaneously affect employee work discipline. Then the independent variables have a significant relationship or employee discipline variables influenced by the variable punisment (X1) and reward (X2). From both result of partial correlation test above seen the biggest punisment variable value compared to reward variable, so the punisment variable is the most dominant variable affecting employee work discipline.  Keywords: Punishment, Reward, Work Discipline